Pengaruh Pengiklanan dan Citra Merek Terhadap Niat Pembelian Produk Ramah Lingkungan Yang Dimediasi Kesadaran Hijau - Albari Albari albari; Tasya Raiihan Firdausi tasya (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to explain the influence of advertising and brand image on the purchase intention of environmentally friendly products mediated by green awareness with the object of research AQUA life. The emergence of the term green marketing is due to the influence of changes in purchasing behavior on people who are starting to implement an environmentally friendly lifestyle due to natural damage that continues to aggravate the earth. The sample used in this study was 166 respondents spread across the territory of Indonesia. The sampling technique used was convenience sampling. The analytical technique used is SEM analysis and processed with the AMOS version 24 application. The results showed that there was a positive and significant influence of green advertising, green brand image, and green awareness on green purchase intentions.